Service dominant logic for actor-to-actor co-creation of value and sustainability outcomes : case studies of five actors in the Swedishlegume industry - Lwin, Eric (SLU/Dept. of Forest Economics, 2022)
Shifts to less energy intensive diets based on plant protein are necessary to meet the food demands of 2050. High protein crops such as legumes are a solution that confers farm-level and societal benefits. However, Sweden lacks the physical, societal, and political infrastructure needed for improved production and consumption. Currently, several market-facing, public and private institutions are acting to innovate and collaborate to develop new products, networks, and systems for market development of legumes and legume-based meat and dairy alternatives. This study explains how actors perceive and act on the environmental, social, and economic potential of legumes through semi-structured interviews. This qualitative data was analysed through the service-dominant logic (SDL) framework with the aim to understand which factors of the legume network need further development. The study involves five actors which include a legume wholesaler, legume-based cheese processor, food system innovation incubator, a multistakeholder network for collaboration and a project for improving school meal systems. Overall, the actors understand the sustainability potential of legumes and show strong collaborative competencies for innovation, marketing, and some national level policy interactions. The results also show the importance of public and private institutions in facilitating transparent resource exchange for the co-creation of value. However, stronger EU-level policy interactions are needed which can influence the sociotechnical regime. Moreover, customer knowledge needs development for improving customer operant resources so that value propositions can be fully understood. Thus, marketers should consider the different product attributes of different legume varieties and legume-based meat and dairy alternatives when developing marketing strategy. This is important when considering trends such as local food which have the potential to be marketed to certain target markets albeit with unclear sustainability trade-offs. To address these issues, the SDL framework suggests that actors should consider coordinated multi-stakeholder collaboration within overlapping institutional logics for comprehensive development of firm strategy, national and EU-level policy for valorising the environmental and social impacts of legume production and consumption for improving farm level viability and customer acceptance